“KEYAKINAN KEPASTIAN KESELAMATAN TERHADAP PELAYANAN PENGINJILAN MENURUT SOTERIOLOGI KRISTEN” - Sahabat, Gracia Gabriella Aurelia (PT. Giat Konseling Nusantara, 2025)
This article discusses the role and influence of the belief in the certainty of salvation in evangelistic ministry according to Christian soteriology. Christian soteriology includes various views on how salvation is obtained and understood. However, fundamentally, the Christian belief states that salvation is obtained through faith in Jesus Christ as Savior and Lord. Belief in the certainty of salvation affects the evangelist's approach in conveying the gospel message to people who do not know Christ. This article explores how these beliefs influence the evangelistic ministry and how the evangelist communicates the message of salvation with unwavering conviction. This article also acknowledges the differences in understanding and beliefs about the assurance of salvation and the importance of considering context and individual needs in evangelistic ministry.